MP33: Provincial spread of buprenorphine/naloxone initiation in emergency departments for opioid agonist treatment: a quality improvement initiative. (May 2020) - McLane, P.; Scott, K.; Yee, K.; Suleman, Z.; Dong, K.; Lang, E.; Fielding, S.; Deol, J.; Fanaeian, J.; Olmstead, A.; Ross, M.; Low, K.; et al.
Abstract : Background: Since January 1, 2016 2358 people have died from opioid poisoning in Alberta. Buprenorphine/naloxone (bup/nal) is the recommended first line treatment for opioid use disorder (OUD) and this treatment can be initiated in emergency departments and urgent care centres (EDs). Aim Statement: This project aims to spread a quality improvement intervention to all 107 adult EDs in Alberta by March 31, 2020. The intervention supports clinicians to initiate bup/nal for eligible individuals and provide rapid referrals to OUD treatment clinics. Measures & Design: Local ED teams were identified (administrators, clinical nurse educators, physicians and, where available, pharmacists and social workers). Local teams were supported by a provincial project team (project manager, consultant, and five physician leads) through a multi-faceted implementation process using provincial order sets, clinician education products, and patient-facing information. We used administrative ED and pharmacy data to track the number of visits where bup/nal was given in ED, and whether discharged patients continued to fill any opioid agonist treatment (OAT) prescription 30 days after their index ED visit. OUD clinics reported the number of referrals received from EDs and the number attending their first appointment. Patient safety event reports were tracked to identify any unintended negative impacts. Evaluation/Results: We report data from May 15, 2018 (program start) to September 31, 2019. Forty-nine EDs (46% of 107) implemented the program and 22 (45% of 49) reported evaluation data. There were 5385 opioid-related visits to reporting ED sites after program adoption. Bup/nal was given during 832 ED visits (663 unique patients): 7 visits in the 1st quarter the program operated, 55 in the 2nd, 74 in the 3rd, 143 in the 4th, 294 in the 5th, and 255 in the 6th. Among 505 unique discharged patients with 30 day follow up data available 319 (63%) continued to fill any OAT prescription after receiving bup/nal in ED. 16 (70%) of 23 community clinics provided data. EDs referred patients to these clinics 440 times, and 236 referrals (54%) attended their first follow-up appointment. Available data may under-report program impact. 5 patient safety events have been reported, with no harm or minimal harm to the patient. Discussion/Impact: Results demonstrate effective spread and uptake of a standardized provincial ED based early medical intervention program for patients who live with OUD.